ANALISIS DAYA DUKUNG FONDASI TAPAK DENGAN MENGGUNAKAN PERKUATAN CERUCUK DIBANDINGKAN DENGAN FONDASI SUMURAN - Ingga Aranka Rizolla; Yayuk Apriyanti (Jurusan Teknik Sipil Universitas Bangka Belitung, 2015)
Foundation footprint included in shallow foundations are often used in multi-storey strukutur by using reinforcement cerucuk . To determine the carrying capacity of the foundation , then do a comparison between the foundation footprint using cerucuk the foundation sinks . Reasons for using the foundation sinks because the foundation is included in the transition from foundation to foundation in shallow foundations. Research to determine the bearing capacity of the foundation conducted using Terzaghi (1943 ), Schertmann (1978 ), Bagmann (1965 ), Mayerhorf (1956 ) and Caisson. Results indicate that the carrying capacity generated by the foundation pitting on the first and second load greater than 1.20 and 1.31 using the retrofitting cerucuk foundation footprint while for smaller decrease by 2.02 and 1.21